MPFL SURGICAL SIMULATION WITH FEMORAL DRILL HOLE ALLOWING FOR ADJUSTABLE GRAFT TENSION. Issue 3 (31st March 2019) - Shea, Cooper; Rustad, Audrey; Anchustegui, Nicolas G.; Troyer, Stockton; Dingel, Aleksei; Shea, Kevin; Ganley, Theodore J.; Milbrandt, Todd A.
Background: In skeletally immature patients, the MPFL femoral origin as near or below the physis in most age groups. Although MPFL reconstruction procedures that employ patella drill holes facilitate graft tension adjustment, recent research demonstrates significant risk of patella fractures if patella drill holes are utilized. For this reason, the use of patella drill holes may be best avoided, but this technical alteration makes graft tension fixation more challenging during MPFL reconstruction in the skeletally immature. The purpose of this study was to evaluate the feasibility of developing a physeal respecting femoral drill for the MPFL origin with surgical model simulation, which allows for graft tensioning during MPFL reconstruction. Methods: Pediatric cadaveric specimens (n=5) were dissected by a group of fellowship trained pediatric and/or sports orthopaedic surgeons, and these specimens were then subject to CT Scans for the creation of 3D models. Specimens, aged 7, 9, 10, 11 and 11 years, were used to develop surgical simulations. CT Scans were loaded into Osyrix, converted to appropriate file structure, and then 3D models were loaded into Blender (Stichting Blender Foundation, Buikslotermeerplein 161, 1025 ETAmsterdam, the Netherlands). These models were used to evaluate 3D models of the knee, with placement of medial femoral condyle drill holes starting at the MPFL femoral origin, and entering the joint just anterior to the PCL femoral origin. The anatomic goals of the surgical simulation include: 1. Place drill hole at the MPFL origin on the femur. 2 Enter the intercondylar notch region of the femur anterior to the PCL origin allowing for arthroscopic visualization. 3. avoiding the articular cartilage on the medial femoral condyle. 4. Avoid the femoral physis throughout the course of drilling from the femoral MPFL Origin point to the entry location into the intercondylar notch. In the specimens, a full length drill hole was placed with either a 4 or 5 mm drill hole. Results: All specimens were subject to the surgical modeling and simulated drill hole placement. In each case, a drill hole was successfully placed meeting all the goals of the simulation: 1. Starting Point at MPFL, 2. Exit point anterior the PCL origin, 3. Exit point posterior to the articular cartilage, and 4. Avoidance of direct physeal injury. Figures 1 and 2. Conclusion: Setting graft tension during MPFL reconstruction is one of the significant technical challenges during MPFL reconstruction, and appropriate graft position and tension may be the most critical elements of successful MPFL reconstruction. Historically, graft tension has been set on the patella, using drill holes for the MPFL attachment point on the patella, but this technique has been associated with patella fractures. In order to allow for adjustment of graft tension on the femoral side of the MPFL graft during surgical reconstruction, a surgical simulation was developed to confirm the anatomic appropriateness and safety of placement of femoral drill holes which allow for adjustment of graft tension. This surgical simulation model confirms that MPFL femoral origin anatomy can be reproduced with injury to the physis, the PCL, or the articular cartilage of the femoral condyle. This drill hole and graft can be visualized arthroscopically and allow for appropriate graft tensioning during the procedure. Figure 1. MFPL Drill Holes starting at Femoral Origin MFPL Drill hole entering the femur, anterior to the PCL Origin, and posterior to the articular cartilage Figure 2. Exit Point of MPFL guide pin or small drill hole, to allow for suture tensioning of the Graft (Yellow Arrow), and avoiding the PCL Fibers (Red Arrow)